Comparison of Frequency of Surgical Site Infection in Patients of Peritonitis Undergoing Laparotomy with Closed Wound and Drain Placed vs Open Wound Without Drain - Nawab, Umar; Ashraf, Imran; Ayub, Aoun; Tahir, Masood; Nawab, Mehreen; Javed, Hamra (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare of frequency of “surgical site infection (SSI)” in patients of peritonitis undergoing laparotomy with abdominal closure with subcutaneous drain placement versus open skin technique without drain. Study Design: Comparative observational study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Mar 2023-2024. Methodology: A total of 240 patients who underwent laparotomy for peritonitis were included in the study and were divided into “abdominal closure with subcutaneous drain Group (A)” and “open skin technique without drain Group (B)”. At 30-days post-operative period, patients were assessed for presence of surgical site/wound infection. Data was analyzed by SPSS 20. Results: Mean age was 40.98±8.81 years. There were 134(55.83%) males and 106(44.17%) were females. Most common reason for peritonitis was “intestinal perforation” 87(36.25%) followed by “perforated appendix” 78(32.50%) and “gastric ulcer perforation” 75(31.25%). In “closed wound with drain Group”/Group A, frequency of SSI was 12(10.00%) while in “open skin technique without drain Group”/Group B, it was 25(20.83%), respectively (p=0.020). Conclusion: Frequency of SSI was significantly lower when wound was closed and a subcutaneous drain was placed as compared to open skin technique without drain.